Defesa da concorrência no Brasil: Aspectos institucionais, desempenho recente e perspectivas de reforma - Lucia Helena Salgado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The essay intends to analyze the competition policy in Brazil after twelve years of the Law n. 8.884/1994, which has effectively inaugurated it. Thus, it initiates with a historical approach, exposing the principal premises that guide this public policy exercise. Utilizing data from the Administrative Council for Economic Defense (Cade), such as condemnations per economic sector and decisions regarding merger and administrative proceedings, attempts to identify the principal obstacles to the effective competition exercise. Finally, is emphasized the convenient moment to review the regulatory framework and expounded the principal points of the Project of Law n. 3.937/2004, with this purpose.
Keywords: K20; L40; N46; 330; Wettbewerbspolitik; Brasilien